POLITIK HUKUM PEMBENTUKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 10 TAHUN 2021 TENTANG FASILITASI PENCEGAHAN, PEMBERANTASAN PENYALAHGUNAAN DAN PERDERAN GELAP NARKOTIKA (P4GN) - Luthfialdo Mu’ayyadi; Gusliana HB; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Drug crime is an International crime, organized crime, has an extensive network,has large financial support and already uses advanced technology. This study aims to findout how the legal policy of the establishment of Regional Regulation Number 10 of 2021concerning Facilitation of Prevention, Eradication of Abuse, and Illicit Circulation ofNarcotics. The formulation of the proposed problem is how legal politics and legal policieswill be in the future in Pekanbaru City Regional Regulation Number 10 of 2021 concerningFacilitation of Prevention, Eradication of Abuse, Illicit Circulation of Narcotics from thepolitical aspect of law.The research used is normative legal research that uses library legal research. Theresults of this study show that in the process of forming regional regulations, there arecertainly reasons, this is in consideration of the formation of Regional Regulations on thePrevention, Eradication of Abuse, and Illicit Circulation can be seen from philosophical,juridical, and sociological foundations. In a formation of a regulation, there must be a namefor addition or commonly referred to as Ius Contiuendum which means a rule or policy thatwill be aspired to, in Pekanbaru City Regional Regulation Number 10 of 2021 concerningFacilitation of Prevention, Eradication of Abuse, and Illicit Circulation of Narcotics, thereneeds to be a legal policy in the future in order to facilitate the prevention, eradication ofabuse, and illicit circulation of narcotics In other words, there is a Rules that need to beadded such as the existence of legal protections for the community to exercise their rights orwhere present in the judicial process, then there is a need to add related rules that explainthe supervision of the circulation of narcotics through food.The suggestion proposed by the author is that it is hoped that the government,especially the pekanbaru city regional government as part of the control of a country andthe originator of policies through legal politics that are carried out should be able to betterdetail the things produced, especially in the legal products produced. So that the policies tobe set can be accepted by the community and become the right solution to problems insociety.Keywords: Legal Politics- Regional Regulation Number 10 of 2021-Formation and IusContuendum